Genome-wide characterization of the seasonal H3N2 virus in Shanghai reveals natural temperature-sensitive strains conferred by the I668V mutation in the PA subunit. Issue 1 (December 2018) - Wei, Dong; Yu, De-Ming; Wang, Ming-jie; Zhang, Dong-hua; Cheng, Qi-jian; Qu, Jie-Ming; Zhang, Xin-xin
Abstract Seasonal H3N2 influenza viruses are recognized as major epidemic viruses, exhibiting complex seasonal patterns in regions with temperate climates. To investigate the influence of viral evolution and mutations on the seasonality of influenza, we performed a genome-wide analysis of samples collected from 62 influenza A/H3N2-infected patients in Shanghai during 2016–2017. Phylogenetic analysis of all eight segments of the influenza A virus revealed that there were two epidemic influenza virus strains circulating in the 2016–2017 winter season (2016–2017win) and 2017 summer season (2017sum). Replication of the two epidemic viral strains at different temperatures (33, 35, 37, and 39 °C) was measured, and the correlation of the mutations in the two epidemic viral strains with temperature sensitivity and viral replication was analyzed. Analysis of the replication kinetics showed that replication of the 2016–2017win strains was significantly restricted at 39 °C compared with that of the 2017sum strains. A polymerase activity assay and mutational analysis demonstrated that the PA I668V mutation of the 2016–2017win viruses suppressed polymerase activity in vitro at high temperatures. Taken together, these data suggest that the I668V mutation in the PA subunit of the 2016–2017win strains may confer temperature sensitivity and attenuate viral replication and polymerase activity; meanwhile, the 2017sum strains maintained virulence at high temperatures. These findings highlight the importance of certain mutations in viral adaptation and persistence in subsequent seasons.